Initial Development of an Electrical Power Generator by using Thermoelectric Generator, Focal Lens and Underground Heat Dissipation System - Syed Zainal Abidin Syed Kamarul Bahrin; Sabarina Jaafar (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Electrical energy is important in various developments to ensure global stability. However, most electrical energy sources are non-renewable and these sources are expected to be depleted in the near future. In order to solve this problem, research on renewable energy sources are intensified and thermoelectric generator (TEG) is one of the potential solutions. TEG can generate electricity if the there is a temperature difference between the hot end and cold end of its plate and it is widely used in various applications, ranging from high temperature of a steam generator until to the lowest temperature of a human body. The initial development of this work focuses on the electrical power generator design by using focal lens to focus sunlight, a form of renewable energy, on the TEG hot end and also underground heat dissipation system on the cold end to create temperature difference. The initial results showed that the amount of power produced by the system is quite small but reasonable due to the type of TEGs used. However, the heat dissipation system showed a promising development due to its non-dependency on external energy to expel heat from the cold side.